¨La motivación en el desarrollo de la inteligencia emocional de los niños de primer año de Educación Básica, de la Escuela Fe y Alegría, Ciudad de Riobamba Provincia Chimborazo, en el año lectivo 2015-2016¨ - Lema González, Margoth Eulalia (2017)
The research was proposed the goal of determining importance of MOTIVATION IN THE DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN CHILDREN OF THE FIRST YEAR OF BASIC EDUCATION IN "FE Y ALEGRÍA" SCHOOL IN RIOBAMBA CITY, CHIMBORAZO PROVINCE, 2015-2016 SCHOOL PERIOD, this process is developed with the intention of improving the development and management of one's own emotions and that of others. For this reason, the proposal consists of the approach of the problem, general objective and specific objectives that the theoretical approach is followed by reference to the contents related to the independent variable that corresponds to the motivation, this is the impulse that leads a person to meet the goals that he/she proposes in his/her daily life, we already know that when there are non-motivated people, it will be more difficult to meet the goals, the dependent variable Emotional Intelligence which is the ability that a person has to recognize and identify his/her own feelings and the ones of others, so that he/she can develop better in society. The methodological framework begins with the inductive deductive method, non-experimental design, the type of investigation is descriptive, field, bibliographic, the level of the research research is diagnostic and exploratory, the sample population is 32 children, the applied technique is to observe the children supported by the observation sheet as an instrument to obtain the results and thus focus on the tabulation of data by statistical tables of the observation process carried out, and this will help us to draw the following conclusions: a child who is not motivated will not be predisposed to a lasting and meaningful learning, it is recommended to always try to predispose the child to playful activities before beginning with cognitive activities.